Advertising dengue : deconstructing the anti-dengue campaign in Singapore. - Chan, Esther Ying'en. (2011)
This study focuses on the deconstruction of the dengue discourse. Dengue fever has been one of the more salient diseases in Singapore after 2005’s outbreak. Since then, the media has been flooded every year with anti-dengue campaigns. Using Critical Discourse Analysis and Foucault’s governmentality framework, I focused on how the government used the campaigns as a hegemonic tool to enter into people’s private homes in a bid to fight dengue, and to inculcate the sense of self-governance amongst the people towards dengue through direct intervention. Findings show that the dengue discourse is built upon the state’s family ideology, rhetoric of control and responsibility, as well as the conceptualizations of risk.